Hormonal effects of swim and resistance training female swimmers - Ferrando, A. A.; Tipton, K. D.; Williams, B. D.; Wolfe, R. R. (Medicine & Science in Sports & Exercise, 1995)
Although an increase in muscular strength is important to swimmers, it is not certain if resistance training provides beneficial effects above those attained with swim-training alone. Six collegiate swimmers were studied to determine if resistance training combined with intense swimming training resulted in hormonal profiles favorable to increased muscle anabolism beyond that which results from swimming alone. Analyses were performed after training sessions combining these elements and/or using the elements alone. The addition of resistance training provided no biochemical advantage over swimming training without resistance training. Implication: The failure to observe differences from strength training in these women adds more fuel to the perception that the magnitude and nature of the "strength training" response is different in females than males. It is of very limited to negligible benefit to women.